Think 'necessarg skills,' not 'print journalism.'. - BRANDT, DAVID (Quill)
The article discusses some suggestions for print journalism majors who want a sustainable career in news media. From the Web-design view, they should learn CSS or the coding language used for presentation, Javascript or the coding language that influences behavior on a website and HTML or the coding language that determines the content read and how it is laid out on the screen. It indicates that part of building a career is to maintain a sense of marketability.